Identical synchronization of a new chaotic system via nonlinear control and linear active control techniques: A comparative analysis - Saaban, Azizan; Ibrahim, Adyda; Shahzad, Mohammad; Ahmad, Israr (SERSC, 2014)
Most of the synchronization techniques belong to the master-slave (drive-response) system configurations in which the two chaotic systems are coupled in such a manner that the performance of the second (slave /response) system is influenced by the first (drive/master) system and the first system is not disturbed by the exertion of the second (slave / response) system.In this research paper, the synchronization problem of two widely used techniques, the Linear Active Control and Nonlinear Control Algorithms have been studied to achieve chaos synchronization of a new chaotic system. In this study, using the Linear Active Control and the Nonlinear Control algorithms and based on the Lyapunov Stability Theory, it has been shown that the two techniques have excellent transient performance and that analytically as well as graphically, the synchronization is asymptotically globally stable.Numerical simulations are furnished to show the efficiency and effectiveness of the two methods.